Autologous stem cell transplantation vs bortezomib based chemotheraphy for the first‐line treatment of systemic light chain amyloidosis in the UK. (27th January 2021) - Sharpley, Faye A.; Manwani, Richa; Petrie, Aviva; Mahmood, Shameem; Sachchithanantham, Sajitha; Lachmann, Helen J.; Martinez De Azcona Naharro, Ana; Gillmore, Julian D.; Whelan, Carol J.; Fontana, Marianna; Cohen, Oliver; Hawkins, Philip N.; et al.
Abstract: Objectives: The benefit of autologous stem cell transplantation (ASCT) in the treatment of light chain (AL) amyloidosis requires re‐evaluation in the modern era. This retrospective case‐matched study compares ASCT to bortezomib for the treatment of patients with AL amyloidosis. Methods: Newly diagnosed patients with AL amyloidosis treated with ASCT or bortezomib between 2001 and 2018 were identified. Patients were excluded if the time from diagnosis to treatment exceeded 12 months. Patients were matched on a 1:1 basis, using a propensity‐matched scoring approach. Results: A total of 136 propensity score‐matched patients were included (ASCT n = 68, bortezomib n = 68). There was no significant difference in overall survival at two years ( P  = .908, HR: 0.95, CI: 0.41‐2.20). For ASCT vs bortezomib: overall haematological response rate at 6 months was 90.6% vs 92.5%; organ response at 12 months: cardiac (70.0% vs 54%, P  > .999), renal (74% vs 24%, P  = .463) liver (21% vs 22%, P  = .048); median progression‐free survival (50 vs 42 months P  = .058, HR: 0.61, CI: 0.37‐1.02) and time to next treatment (68 vs 45 months, P  = .145, HR: 0.61, CI: 0.31‐1.19). More patients required treatment in the bortezomib group compared to ASCT group at 24 months (41 vs 23, Chi‐squared P  = .004) and 48 months (57 vs 41, Chi‐squared P  = .004). Conclusions: This small retrospective study suggests that there is no clear survival advantage of ASCT over bortezomib therapy. A prospective randomised controlled trial evaluating ASCT in AL amyloidosis is critically needed.